The effect of financial ratios on stock returns in companies in the banking sector listed on the Indonesian Stock Exchange for the period 2020-2024 - Hedjri Samuel Putra Lubis; Bambang Satriawan; Benni Sumarman (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study aims to examine the effect of Quick Ratio (QR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on stock returns of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research evaluates how liquidity, leverage, and profitability indicators influence investor responses and stock performance in the banking sector. Methodology/approach: This quantitative study uses secondary data from 29 banking companies meeting purposive sampling criteria, producing 145 observations. Multiple linear regression with the Ordinary Least Squares (OLS) method was applied after conducting classical assumption tests. The dependent variable is stock return, while QR, DER, and ROE serve as independent variables. Results/findings: Findings show that the Quick Ratio has no significant partial effect on stock returns. The Debt to Equity Ratio exhibits a negative but marginally insignificant effect. Return on Equity is the only variable with a positive and significant effect on stock returns. Simultaneously, QR, DER, and ROE significantly influence stock returns, with ROE being the dominant predictor. The Adjusted R² value indicates that 18.3% of stock return variation is explained by the model. Conclusion: Profitability, reflected through ROE, is the primary determinant of banking stock returns, while liquidity and leverage show limited explanatory power. Investors prioritize profitability over liquidity and capital structure in assessing banking performance. Limitations: This study uses only three financial ratios, excludes macroeconomic and firm-specific control variables, and focuses solely on the banking sector during one period. Contribution: The research strengthens empirical evidence on profitability’s role in influencing stock returns and provides guidance for investors and banking management regarding financial indicators that shape market valuation.